Contemplating Grace: Memories from a Manuscript (Catalogue and Interdisciplinary Study of Tufts University Ms. 2, Hours of the Virgin). - Travers, Mary G. (Tufts Archival Research Center, 2018)
This senior honors thesis is an interdisciplinary examination of a Late Medieval Book of Hours, which is the first published study and codification of the manuscript. The paper seeks to define the manuscript’s context of production, while examining its bicultural environment, the role images played in Medieval prayer, and the organic nature of the book itself.